Función eréctil en varones con hipertrofia benigna de próstata en tratamiento con tamsulosina - Olazabal Chavesta, Pedro Hans (2017)
Benign prostatic hypertrophy is a more frequent, complex and progressive urological disease of men, which presents with symptoms of the lower urinary tract and which compromises the quality of life of the patient, producing sexual dysfunction in its different domains. OBJETIVE: Determine if there is difference in erectile function in men with BPH diagnosis before and after treatment with tamsulosin. MATERIALS AND METHODS: We analyzed 57 patients with benign prostatic hypertrophy between 45 and 70 years. They were assessed using the IPSS and IIEF-5 questionnaires at the beginning of the study and after 3 months of receiving treatment with tamsulosin. RESULTS: Erectile function before treatment was 8.8% without erectile dysfunction, 61.4% with mild dysfunction, 26.3% mild to moderate, and 3.5% moderate; at 3 months with treatment was 33.3% without dysfunction, 56.1% mild and 10.5% mild to moderate. There was significant improvement (p <0.001). Statistical analysis was performed using the McNemar-Bowker chi-square test for related samples, with a level of significance of 5%. CONCLUSIÓN: There was improvement in erectile function when comparing patients with BPH before and after treatment with tamsulosin